Synthesis, characterization and testing of nano-structured particles for effective impact modification of glassy amorphous polymers - Van Zyl, A. J. P. (Andries Jakobus Petrus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2003.